Pendampingan Pelatihan Media Digital untuk Meningkatkan Kompetensi Guru Bahasa Arab - Rahmawati, Fatya Nia (TAAWUN, 2024)
In facing the digital era, Arabic language learning needs to follow developments in technology and digital media. The use of digital media in the learning process can provide a more interesting and effective learning experience for students. This Community Service activity aims to analyze teacher assets in increasing competency, and development strategies carried out, as well as knowing the results to be achieved in mentoring digital media training. The method used in this community service is Asset-Based Community Development (ABCD). The stages in this service are inculturation, discovery, design, definition and reflection. The results of this community service are (1) Teacher assets in increasing competency are attitude, collaborative spirit and motivation to continue learning, (2) the development strategy implemented in Digital Media Training Assistance to Increase the Competency of Arabic Language Teachers in Bojonegoro is the inculturation stage up to the implementation, strategies involve identification of local potential, utilization of the Appreciative Inquiry method, collaboration with stakeholders, and an interactive approach in training, and (3) the results achieved in Digital Media Training in Bojonegoro include a positive transformation in teacher skills . It is hoped that teachers will become more adept at using digital media, creating more engaging learning experiences, and increasing student engagement. In addition, the results achieved involve the continued adoption of technological developments in learning, creating a sustainable long-term impact.